Women in Mexican folk art : of promises, betrayals, monsters and celebrities - Bartra, Eli (Iberian and Latin American studies., 2011)
"Mexico is home to some of the world's most extraordinary folk art, and the majority of its highly acclaimed pieces were created by women. Looking closely at eight types of Mexican folk art, including votive paintings, embroidered exvotos, cardboard Judas dolls, reproductions of Frida Kahlo's paintings made of clay, and clay figures from Cumicho called alebrijes, this beautifully illustrated volume is one of the first to trace the role and effects of gender on both the objects of Mexican folk art and the knowledge and life experiences that lie behind them."--